Coat proteins of necroviruses target 14-3-3a to subvert MAPKKKα-mediated antiviral immunity in plants - Zongyu Gao; Dingliang Zhang; Xiaoling Wang; Xin Zhang; Zhiyan Wen; Qianshen Zhang; Dawei Li; Savithramma P. Dinesh-Kumar; Yongliang Zhang (Nature Communications, 2022)
MAPK cascades play an important role in innate immunity. Here, the authors show that that beet black scorch virus activates MAPK signaling in Nicotiana benthamiana and the viral coat protein counteracts MAPK-mediated defence by competitively binding to a MAPKKKα interactor.